Principles of building a system for automating the activities of a process engineer based on an ontological approach within the framework of the industry 4.0 concept - Taberko, Valery; Ivaniuk, Dzmitry; Zotov, Nikita; Orlov, Maksim; Pupena, Alexander; Lutska, Natalia (My University, 2021)
In this article, an approach to the continuous development of automation of the processes of creating, developing and applying standards based on the OSTIS Technology is proposed. Examples of these processes due to the involvement of end-users of the system using the tools and mechanisms of the OSTIS Technology are considered. Examples of further formalization of standards within the framework of the proposed approach are given.
Keywords: automation of manufacturing processes; knowledge base; information service; ontological production model; industry 4.0; ontology; автоматизація виробництва; інформаційне обслуговування; онтологічна модель виробництва; промисловість 4.0; онтологія; база знань; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка